Landscape Plotted and Pieced Landscape History and Local Archaeology in Fyfield and Overton, Wiltshire - Fowler, Peter (Reports of the Research Committee of the Society of Antiquaries of London, 2000)
This book presents the results of 39 years of study of the two Wiltshire parishes of Fyfield and Overton Down. The aim of the project, using a diverse range of research methods, from archaeological excavation and experimental archaeology through the study of environmental and documentary evidence to the non-invasive techniques of geophysics and air photography, was to elucidate how and when the landscape came by its present appearance. The author draws three illuminating conclusions from this investigation. First, very little, if any, of this landscape is now "natural": it has been created by the agricultural activities of successive communities over the last 6,000 years. Second, the nature of this "artefact" has been, and continues to be, influenced by the geology, hydrology, soils and climate of the area. Finally, the principal land-use features of the present landscape were established at particular times over the last four millennia, and that what has come to be seen as a quintessentially "English" landscape was in fact set some 1,500 years ago.